THE RELATIONSHIP BETWEEN PHYSICO-CHEMICAL CHARACTERISTICS OF GROUND AND BIOMETRICS ROSEHIP FRUITS - Sorina ROPCIUC (Stefan cel Mare University of Suceava, 2019)
Soil analysis was determined in order to identify the type of soil through nutrient analysis and granulometric analysis, features that may occur in the fructification of the species Rosa canina L. The studied area includes the Plateau of Suceava and Obcina Mare, where the lowest elevation is in the floodplain area of Suceava (292 m) and in Dărmănești station and the highest research point is Palma with an altitude of 1080 m. The field gradient is between 0.1 ° and 13.4 °, the dominant slopes have values of 0.8 ° and 2.6 ° and they are characteristic to the plateau of Suceava. The assessment of geodeclivity was obtained based on grid information using GIS software. The obtained results led to the classification of the studied soils based on fertility; statistical interpretation has been made in terms of influence of soil fertility on the fructification of Rosa canina L. By using statistical PCA and MCA programs we were able to classify soils by chemical constituents. The correlation index determined by Pearson matrix showed a significant correlation level between the chemical characteristics of soil and the productivity of rosehip bushes.